The Relationship Between Social Support and Relapse Tendency Among Those Who Struggle With Drug Addiction: Multiple Mediators of Exercise Self-Efficacy and Health-Related Quality of Life - Jia, Dongming (Journal of drug issues, 2024)
Based on social support theory and exercise promotion health theory, we verified the mediating role of exercise self-efficacy and health-related quality of life in the relationship between social support and the relapse tendency of Chinese people who struggle with drug addiction. Samples who had received traditional Chinese health-promoting exercise interventions over 3 months were recruited from two drug rehabilitation centres in Zhejiang Province (n = 415). The participants completed the Social Support Rating Scale, Exercise Self-Efficacy Scale, Health Survey Short Form Questionnaire Chinese version, and Relapse Tendency Scale. Correlation analysis showed significant positive correlations between social support, exercise self-efficacy, and quality of life. In contrast, social support, exercise self-efficacy, and quality of life were negatively correlated with relapse tendency. In addition, intermediary effect analysis showed that social support has a direct negative predictive effect on relapse tendency in two ways: as an independent intermediary of exercise self-efficacy and as a chain intermediary of exercise self-efficacy and quality of life. Good exercise habits and adherence, as well as early establishment of social support, are beneficial not only for reducing craving and relapse behaviour but also for enhancing the quality of life of people who struggle with drug addiction, thereby facilitating the recovery efficacy for maintenance.